The influence of word of mouth and green marketing on purchase intention with brand image as a mediating variable - Sinta Puspitasari, Dewi; Noviarakhman Zagladib, Arief (Universitas Islam Lamongan, 2024)
This study aims to examine the impact of Word of Mouth and Green Marketing on Purchase Intention, with Brand Image serving as a mediating variable. The research focuses on Generation Z (aged 20-24 years) in Malang City, specifically users of Lee Minerale bottled water. The research is explanatory in nature, seeking to clarify the causal relationships among various variables. The population for this study includes 64,130 individuals within the specified age group in Malang City, based on BPS data from 2023. The sample was selected using nonprobability sampling with a purposive sampling technique. The study employs a quantitative approach, with data collected through questionnaires and measured using a Likert scale. Hypothesis testing was conducted using the t-test to determine whether the independent variables significantly influence the dependent variable. The findings indicate that all variables have an impact, though Green Marketing does not significantly affect Purchase Intention.